BELGOROD SCHOOL OF RESEARCHERS OF SOCIAL TECHNOLOGIES - Valentin P. Babintsev (Moscow Polytechnic University, 2016)
The article highlights the problem of the theory development and implementation of social technologies on the example of the scientific school at National Research University Belgorod State University. In 1990 L. Dyatchenko and N. Danakin created the chair of social technologies at Belgorod technological institute and became the leaders of the group of scholars. Later the school continued the researches at BelSU. According to the presented approach social technologies are viewed as a continuation and application of the general principles of production to the society functioning taking into account its specificity. The main results of scientific researches, challenges in scientific-theoretical, socio-cultural and practical sphere have been analyzed.